2017
DOI: 10.1186/s12917-017-0999-2
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole for the treatment of Tritrichomonas foetus in bulls

Abstract: Background Tritrichomonas foetus is a sexually transmitted protozoon that causes reproductive failure, among cattle, so disruptive that many western US states have initiated control programs. Current control programs are based on the testing and exclusion of individual bulls. Unfortunately, these programs are utilizing screening tests that are lacking in sensitivity. Blanket treatment of all the exposed bulls and adequate sexual rest for the exposed cows could provide a more viable disease control option. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Besides, the FDA currently prohibits its use in all food-producing animals. This institution has the authority to prohibit "the extralabel use of the drug or drug class presents a public health risk" in his case, due to its potential to cause cancer in humans (Love et al, 2017). As a consequence, there is currently no effective therapy for BT (Carvalho & Gadelha, 2007;Bader et al, 2016) and no vaccine has yet been developed to prevent the disease (Hairgrove et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the FDA currently prohibits its use in all food-producing animals. This institution has the authority to prohibit "the extralabel use of the drug or drug class presents a public health risk" in his case, due to its potential to cause cancer in humans (Love et al, 2017). As a consequence, there is currently no effective therapy for BT (Carvalho & Gadelha, 2007;Bader et al, 2016) and no vaccine has yet been developed to prevent the disease (Hairgrove et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Indiscriminate use of trichomonicidal drugs, under-dosage and lack of post-treatment controls have led to failures in therapeutic e cacy and chemoresistant strains (Campero CM, 2006). In addition, the FDA prohibits its application intended for food production (Love et al, 2017). Currently, there is no 100% effective treatment against BT (Carvalho & Gadelha, 2007), so it is usually decided not to treat sick bulls but send them to slaughter instead.…”
mentioning
confidence: 99%
“…Although highly specific and sensitive diagnostic tools have been developed, success is restricted in field conditions [3]. Recently, a single polymerase chain reaction (PCR) test has been used for the regular examination of herds in developed countries, such as Australia, China, and United States of America (USA), which has a sensitivity of 78%-96.7% compared with cultures, and accurately identifies infected populations [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…), the Ministry of Agriculture of the People's Republic of China, and the U.S. Food and Drug Administration (FDA) due to their extreme danger to both human and animal health as well as their propensity to aggregate in aqueous media. 5,6 IARC reported that MNZ causes animal cancer due to MNZ present in feed supplements. However, no data is yet available on MNZ inducing carcinogenicity in human beings.…”
Section: Introductionmentioning
confidence: 99%